giúp mình với
B=(2/15+5/3-3/5):(14/3-5/2)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
a) \(x.\dfrac{3}{4}=\dfrac{9}{14}\)
\(\Rightarrow x=\dfrac{9}{14}:\dfrac{3}{4}\)
\(\Rightarrow x=\dfrac{6}{7}\)
b) \(x:\dfrac{5}{9}=\dfrac{3}{10}\)
\(\Rightarrow x=\dfrac{3}{10}.\dfrac{5}{9}\)
\(\Rightarrow x=\dfrac{1}{6}\)
A= 2/5 - 1
= -3/5
B= -30/24 + 4/24 - 36/24
= 31/12
A = 3/7 x 2x7/3x5 - 3x6/7x3 x 7/6 = 2/5 - 3/3 = 2/5 - 5/5 = -3/5
B=1/6 - (5/4 + 3/2) = 1/6 -(5/4 + 6/4)= 1/6 - 11/4 = 2/12 - 33/12 = - 21/12
a) \(\frac{3}{5}:\left(-\frac{1}{15}-\frac{1}{6}\right)+\frac{3}{5}:\left(-\frac{1}{3}-1\frac{1}{15}\right)\)
\(=\frac{3}{5}:\left(-\frac{1}{15}-\frac{1}{6}-\frac{2}{6}-1+\frac{1}{15}\right)\)
\(=\frac{3}{5}:\left(-\frac{1}{2}-1\right)\)
\(=\frac{3}{5}:\left(-\frac{3}{2}\right)\)
\(=-\frac{2}{5}\)
b) \(\left(-\frac{3}{4}+\frac{5}{13}\right):\frac{2}{7}-\left(2\frac{1}{4}+\frac{8}{13}\right):\frac{2}{7}\)
\(=\left(-\frac{3}{4}+\frac{5}{13}-2+\frac{1}{4}+\frac{8}{13}\right):\frac{2}{7}\)
\(=\left(-\frac{1}{2}+1-2\right):\frac{2}{7}\)
\(=\left(-\frac{1}{2}-1\right):\frac{2}{7}\)
\(=-\frac{3}{2}:\frac{2}{7}\)
\(=-\frac{21}{4}\)
a. \(\frac{9^{15}}{3^{14}.27^6}=\frac{3^{30}}{3^{32}}=\frac{1}{3^2}=\frac{1}{9}\)
b. \(\frac{14^5.8^3}{2^{10}.7^9}=\frac{2^5.7^5.2^9}{2^{10}.7^9}=\frac{2^{14}.7^5}{2^{10}.7^9}=\frac{2^4}{7^4}=\left(\frac{2}{7}\right)^4=\frac{16}{2401}\)
-4/5 + 11/3 - 9/10 =(-4/5 + 11/3) -9/10 =43/15 -9/10 =59/30 5/6 + -7/15 - 13/30 =(5/6 + -7/15) -13/30 =11/30 - 13/30 =-1/15 CHÚC EM HỌC TỐT ^_^
\(\frac{4}{5}\)+ \(\frac{1}{5}\): \(\frac{-2}{15}\)= \(\frac{4}{5}\)+ \(\frac{1}{5}\)* \(\frac{-15}{2}\)=\(\frac{4}{5}\) + \(\frac{-3}{2}\)= \(\frac{-7}{10}\)
b = \(\frac{-7}{12}\). (\(\frac{3}{11}\)+ \(\frac{-14}{11}\)) + \(\frac{5}{6}\)= \(\frac{-7}{12}\). (-1) + \(\frac{5}{6}\)= \(\frac{7}{12}\)+ \(\frac{10}{12}\)= \(\frac{17}{12}\)
|7 - \(\dfrac{3}{4}\)\(x\)| - \(\dfrac{3}{2}\) = \(\dfrac{1}{\dfrac{1}{2}}\)
|7 - \(\dfrac{3}{4}x\)| - \(\dfrac{3}{2}\) = 2
|7 - \(\dfrac{3}{4}\)\(x\)| = 2 + \(\dfrac{3}{2}\)
|7 - \(\dfrac{3}{4}x\)| = \(\dfrac{7}{2}\)
\(\left[{}\begin{matrix}7-\dfrac{3}{4}x=\dfrac{7}{2}\\7-\dfrac{3}{4}x=-\dfrac{7}{2}\end{matrix}\right.\)
\(\left[{}\begin{matrix}\dfrac{3}{4}x=7-\dfrac{7}{2}\\\dfrac{3}{4}=7+\dfrac{7}{2}\end{matrix}\right.\)
\(\left[{}\begin{matrix}\dfrac{3}{4}x=\dfrac{7}{2}\\\dfrac{3}{4}x=\dfrac{21}{2}\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=\dfrac{14}{3}\\x=14\end{matrix}\right.\)
5 - |\(x-3\)| = 5
|\(x-3\)| = 5 - 5
|\(x-3\)| = 0
\(x-3\) = 0
\(x\) = 3
\(B=\left(\frac{2}{15}+\frac{5}{3}-\frac{3}{5}\right):\left(\frac{14}{3}-\frac{5}{2}\right)\)
\(B=\left(\frac{2}{15}+\frac{25}{15}-\frac{9}{15}\right):\left(\frac{28}{6}-\frac{15}{6}\right)\)
\(B=\frac{6}{5}:\frac{13}{6}\)
\(B=\frac{6}{5}.\frac{6}{13}\)
\(B=\frac{36}{65}\)